Human utilisation and environmental quality of wetlands: the case of Harare, Zimbabwe - Mandishona, Emmah (My University, 2017)
Most wetlands in urban environments, especially metropolitan cities in developing countries like Zimbabwe, are being threatened by human activities. This study investigates human understanding and perceptions on wetlands and assessing environmental effects of human utilisation of the wetlands as a means of evaluating their sustainability. A mixed methods approach which entails both quantitative and qualitative methods was used to collect data from human and physical environments of two wetlands in Harare, Zimbabwe. Convenience and snowball sampling were used to select participants for questionnaires, interviews and focus groups. The study used two sets of similar questionnaires to collect data from 40 Borrowdale and 39 Belvedere wetland users and residents. Interviews were also administered to 10 Borrowdale and 12 Belvedere wetland users. Two focus group discussions were administered for Borrowdale and one was administered for Belvedere. Wetland delineation and land use mapping were done using a hand-held GPS. Sediment samples were collected from the utilised and unutilised parts of the two wetlands and were tested for sediment grain size and organic carbon content. Results showed an increase in urban wetland utilisation driven by complex economic, social and political issues. The majority of respondents showed that they were aware of the economic and socials benefits of wetland and environmental effects of different land uses on wetlands. Some respondents were sceptical about some of the environmental benefits of wetlands. Respondents were also aware of negative changes of wetland properties (soil, water, vegetation, birds and animals) due to different land uses on wetlands. Low percentages of organic carbon content in sediments from utilised parts of both wetlands reflected deterioration in soil fertility. There is poor dissemination of knowledge about wetlands to the general public, and existing wetland legislation is not effectively implemented. The study recommends that the government of Zimbabwe should: change its wetland management strategies, review the Environmental Management Act, enact a national wetland policy which involve decisions from all stakeholders, investigate institutions that facilitate wetland laws implementation, and change strategies used and people involved in educating and disseminating information about wetlands. Keywords: vleis, human perceptions, land uses, wetland ecosystems, soil grain size, organic carbon content, wetland elements, wetland values and benefits
Dissertation submitted to Faculty of Science, University of the Witwatersrand, in fulfilment of the requirements for the degree of Masters of Science by research, 2017